Learning Chemistry by ICT (Virtual Animation) at Maumere High School, East Nusa Tenggara - Yusnidar Yusuf (STKIP Singkawang, 2017)
This research was aimed to create attractive learning atmosphere which can make students excited inside theclass.Education was a right for every nation. It had to be given to improving a nation. Chemistry subject, especially in hydrocarbon chapter, was less-favorable by most students due to its difficulty level. Learning outcomes score were low. Many research showed that various method, strategy or another approach in teaching chemistry subject had significantlyimproved towards learning theoutcome of students. One of the approaches was by virtual animation as part of ICT. Based on data result analysis from this research, there was 0,000 < α = 0.05 significance. As result, H0 was rejected. Itmeans that there was significant improve learning outcome using multimedia animation. The role of ICT as learning model should be utilised for granted by teachers to enriched chemistry science in school’s scope.